2015
DOI: 10.1080/10942912.2015.1020434
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Porcine Contamination in Laboratory PrepareddendengUsing Mitochondrial D-Loop686 andcyt bGene Primers by Real Time Polymerase Chain Reaction

Abstract: The identifications of species in meat products have created interests since these foods became the target of forgery and fraud in the market. The presence of pork in food products is not allowed for the Muslim community. Hence, an analysis is necessary to detect the presence of pork in processed meat products, such as in dendeng (dried meat) product. Real time polymerase chain reaction using mitochondrial displacement loop686 and cytochrome b (cytb) gene primers was used to identify specific pork DNA among ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
0
23
0
6
Order By: Relevance
“…The cytb gene primers also had a similar ability with d-Loop686 primer to amplify pork DNA until the pork concentration was of 0.5% in beef "dendeng". The results showed that these two primers, d-Loop region and the cyt b gene, had the capability to identify pork adulteration on the mixed pork-beef "dendeng" product at all variations of tested concentrations [42].…”
Section: Confirmation Of Pig Species Using Real-time Pcrmentioning
confidence: 91%
See 2 more Smart Citations
“…The cytb gene primers also had a similar ability with d-Loop686 primer to amplify pork DNA until the pork concentration was of 0.5% in beef "dendeng". The results showed that these two primers, d-Loop region and the cyt b gene, had the capability to identify pork adulteration on the mixed pork-beef "dendeng" product at all variations of tested concentrations [42].…”
Section: Confirmation Of Pig Species Using Real-time Pcrmentioning
confidence: 91%
“…Animal Species PCR assay for the identification of animal species in feedstuffs [51] Analysis of rat's meat DNA Authentication of beef meatball from rat's meat [52] Analysis of pork DNA in dendeng Authentication of "dendeng" from pork [42] Analysis of porcine gelatin Analysis of porcine gelatin in capsule shell [53] Analysis of pork in meatball Authentication of beef meatball from pork [34] Analysis of pork DNA Identification of pig species in food product [1] Quantification of bovine, porcine, chicken and turkey species Contamination and adulteration prohibited component in food and feed [54] Porcine Gelatin Using gelatin in pharmacy and confectionery [55] Table 3. Analysis of porcine species-based PCR technology on commercial samples.…”
Section: Species Analysis Issues Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengan kemajuan ilmu pengetahuan dan teknologi modern, mulai ada produk makanan yang dicampur dengan bahan non-halal (Van der Spiegel et al, 2012;Schieber, 2008). Sebagian besar komponen non-halal yang ditemukan di pasar adalah daging babi, lemak babi, gelatin babi, dan produk-produk berbasis babi (Maryam et al, 2016;Rahmawati et al, 2016;Sudjadi et al, 2016). Bahan-bahan yang terdapat dalam produk makanan, farmasi atau produk kosmetika dapat bersifat diperbolehkan untuk dikonsumsi secara hukum Islam (halal) atau dilarang dikonsumsi menurut hukum Islam (haram) (Mursyidi, 2013;Raraswati et al, 2013).…”
Section: Pendahuluanunclassified
“…There are several types of PCR including PCR-RAPD, PCR-RFLP and PCR primer specific and real-time PCR. These techniques have been reported the presence of porcine in food including PCR primer specific [3][4]; PCR-RFLP [5][6], PCR-RAPD [7][8], real-time PCR [9][10]. In case of detection of mice, only a few work has been reported.…”
Section: ■ Introductionmentioning
confidence: 99%